Correlation of serum homocysteine levels and lipid profile in coronary heart disease - Awan, Ayesha Naureen; Imtiaz, Humaira; Taimoor, Alruba; nazir, Aamir; Ahmed, Malik Mahmood; Awan, Sarmud Latif (Pakistan Journal of Physiology, 2019)
Background: Coronary heart disease occurs when cholesterol accumulates on the artery walls, creating plaques. Reduced blood flow occurs when one or more of these arteries become partially or completely blocked. Homocysteine is an intermediate formed during the catabolism of methionine. Development of atherosclerotic change is common feature in patients with hyperhomocysteinemia. This study was conducted to access the relationship of Hcy, lipid profile and CHD in our population. Methods: This cross-sectional analytical study was carried out at Biochemistry Department, Ayub Medical College, Abbottabad. Eighty subjects were divided into 2 groups. Cases: 40 patients were confirmed MI patients. Controls: 40 were age and gender matching healthy individuals. Lipid profile and serum total Hcy were measured. Results: The mean age of the cases was 59.68±8.06 years. The controls were 58.93±6.93 years. Mean tHcy level of the cases was 17.15±4.45 ?mol/l while that of controls was 12.20±2.53 ?mol/l (p<0.001). In lipid profile TG and VLDL-C showed a statistically significant rise (p<0.05) in the cases compared to controls. There were statistically significant differences between HDL-C, LDL-C and TC/HDL-C ratios (p<0.001). Mean TG in cases was 166.01±30.03 mg/dl with (p<0.05). Similarly the mean VLDL-C in cases was 33.20±6.01 mg/dl and in controls it was 30.48±2.80 mg/dl (p<0.05). Mean TC in cases was 212.82±32.48 mg/dl and in controls it was 202.80±17.03 mg/dl (p>0.05) which is statistically not significant. Conclusion: Plasma tHcy level and deranged lipid profile are powerful predictor value of CHD but they are independent risk factors.